Demographic structure and spatial pattern of Araucaria angustifolia (Bertol.) Kuntze (Araucariaceae) population in Santa Catarina Estrutura demográfica e padrão espacial de uma população natural de Araucaria angustifolia (Bertol.) Kuntze (Araucariaceae), nareserva genética florestal de caçador, estado de Santa Catarina - Paludo G.F.* (2009)
The Araucaria angustifolia (Bertol.) Kuntze is a Brazilian native species considered threatened. There is a lack of information and data about the species ecology that could be used as the basis for preservation and management measures. Intending to alleviate the this lack of data, this study was carried out based on a natural population of A. angustifolia occurring in the Forest Genetic Reserve of Caçador, located in the Brazilian state of Santa Catarina. The main goal of the present work was to describe the demographic structure of a natural A. angustifolia population. Therefore, the population studied was divided into four classes based on stage and gender: regeneration, juveniles, males and females. The diametric and height structures, sexual ratio, spatial and dependence patterns were evaluated. The results demonstrated that there was a small regeneration ratio and the sexual ratio was around 1:1, as previously expected for the species. In the spatial pattern analysis, aggregation groups appear in all classes studied. The regeneration showed clusters that do not seem to be associated to adult specimens. The natural regeneration occurs, but in low density under forest conditions.